REVIEW: POTENTIAL OF RED BETEL LEAVES (Piper crocatum) AS ANTI-INFLAMMATORY IN Rheumatoid Arthritis - Novia Misnawati Aisyiyah; Khalish Arsy Al Khairy Siregar; Paula Mariana Kustiawan (Jurnal Farmasi Sains dan Praktis, 2021)
Indonesia is a country with fertile soil and rich in plant species. Currently in society the use of medicinal plants as herbal treatment has increased. Elderly people often experience Rheumatoid Arthritis, which is inflammation of the synovial lining of the joints. One of the plants used by the community is red betel leaf (Piper crocatum). However, scientific information related to the potential of red betel as an anti-inflammatory in Rheumatoid Arthritis is still not widely known by the public. This study was conducted to explore the potential of P. crocatum leaves to treat Rheumatoid Arthritis which can be used as references regarding Rheumatoid Arthritis therapy. This study uses a narrative review method from previous studies that were collected related to the topic which was then discussed systematically. By using keywords in the search for Piper crocatum, anti-inflammatory activity, red betel bioactivity, secondary compounds in red betel leaf, and Rheumatoid Arthritis. P. crocatum leaves contain various bioactive compounds. Flavonoids have activity as primary and secondary antioxidants. Flavonoid compounds such as brazilien, brazilin, taxifolin, procyanidin found in red betel have anti-inflammatory activity in rheumatoid arthritis. Brazilin is one of the flavonoid compounds from P. crocatum leaves that has the potential as an anti-inflammatory in rheumatoid arthritis by regulating the transcription factor nuclear factor kappa B (NF-kB) for TNF- expression against inflammation.